Potensi Tanaman Refugia dalam Meningkatkan Keanekaragaman Serangga pada Pertanaman Padi Sawah di Padang Pariaman, Sumatera Barat - Widya Nawir; Novri Nelly; Yaherwandi Yaherwandi (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2021)
Some flowering plants like common zinnia (Zinnia elegans (Jacq) Kuntze), marigold (Tagetes erecta Linnaeus), and cockscomb flowers (Celosia sp.) have been used as refugia and conservation plants for predators and parasitoids but are still not yet optimal. Planting refugia plants can affect insect diversity and evenness index, affecting the stability and balance of the agroecosystem. The study aimed to determine the effect of common zinnia, cockscomb flowers, and marigold as refugia on insects’ diversity and evenness index and their potential as a medium for conservation of predators and parasitoids. The study was conducted in organic rice fields in Batang Anai Sub-district, Padang Pariaman District, West Sumatra, from May to July 2020. The Insect was collected from plots covering an area of ??48 m2 and identified in the Bioecology laboratory, Faculty of Agriculture, Universitas Andalas. Planting common zinnia, marigolds, and cockscomb flowers increased the index of diversity and evenness of insects around rice fields. The index of diversity and evenness of insects on cockscomb flowers (H = 2.90) was higher than that of common zinnia (H = 2.61) and marigold (H = 2.63). Cockscomb flowers have more potential as a medium for conserving predators and parasitoids.